The Question Of The Instrument Concerto In Uzbek Composing And Of Form In Instrumental Ensembles - Mirzohid Bazarov (Peerian Journals Publishing, 2024)
This article describes the problems and successes of the instrument concert and chamber instruments in Uzbek compositional creativity, interprets their scientific and creative principles, describes author's works, proves them from a scientific point of view, studies of the form issues of the instrument concert and its musical expressive means, comparative analysis of concerts for piano and orchestra on world music history, interprets the, their structure and innovations are covered and analyzed scientifically and creatively.
Keywords: music; art; instrumental performance; composer